Analysing patent landscapes in plant biotechnology and new plant breeding techniques - Parisi, Claudia; Rodríguez-Cerezo, Emilio; Thangaraj, Harry (Transgenic research, 2013)
This article aims to inform the reader of the importance of searching patent landscapes in plant biotechnology and the use of basic tools to perform a patent search. The recommendations for a patent search strategy are illustrated with the specific example of zinc finger nuclease technology for genetic engineering in plants. Within this scope, we provide a general introduction to searching using two online and free-access patent databases esp@cenet and PatentScope. The essential features of the two databases, and their functionality is described, together with short descriptions to enable the reader to understand patents, searching, their content, patent families, and their territorial scope. We mostly stress the value of patent searching for mining scientific, rather than legal information. Search methods through the use of keywords and patent codes are elucidated together with suggestions about how to search with or combine codes with keywords and we also comment on limitations of each method. We stress the importance of patent literature to complement more mainstream scientific literature, and the relative complexities and difficulties in searching patents compared to the latter. A parallel online resource where we describe detailed search exercises is available through reference for those intending further exploration. In essence this is aimed at a novice patent searcher who may want to examine accessory patent literature to complement knowledge gained from mainstream journal resources.